Genome-wide identification of A-to-I RNA editing events provides the functional implications in PDAC - Mei, Yue; Liang, Dong; Ai, Bin; Wang, Tengjiao; Guo, Shiwei; Jin, Gang; Yu, Dong (Frontiers in Oncology, 2023)
RNA editing, a wide-acknowledged post-transcriptional mechanism, has been reported to be involved in the occurrence and development of cancer, especially the abnormal alteration of adenosine to inosine. However, fewer studies focus on pancreatic cancer. We aimed to explore the possible linkages between altered RNA editing events and the development of PDAC. We characterized the global A-to-I RNA editing spectrum from RNA and matched whole-genome sequencing data of 41 primary PDAC and adjacent normal tissues, revealing a large number of adaptive RNA editing events with significant differences in editing levels, which are mainly regulated by ADAR1. The results showed that, in general, RNA editing in tumors has a higher editing level and more abundant editing sites. 140 genes were screened out since they were identified with significantly different RNA editing events and were significantly different in expression level between tumor and matched normal samples. Further analysis showed a preference that in the tumor-specific group, they are mainly enriched in cancer-related signal pathways, while in the normal tissue-specific group, they are mainly enriched in pancreatic secretion. At the same time, we also found positively selected differentially edited sites in a series of cancer immune genes, including EGF, IGF1R, and PIK3CD. RNA editing might participate in pathogenisis of PDAC through regulating the alternative splicing and RNA secondary structure of important genes to further regulate gene expression and protein synthesis, including RAB27B and CERS4. Furthermore, single cell sequencing results showed that type2 ductal cells contributed the most to RNA editing events in tumors. According to the analysis of differential editing sites, it can be determined that RNA editing is an epigenetic mechanism involved in the occurrence and development of pancreatic cancer. It has the potential to diagnose of PDAC and is closely related to the prognosis.